Importance and health benefits of millets in present scenario: A superfood and forgotten grains - Kakran, Jyoti; Rani, Seema (International Research Journal of Ayurveda & Yoga, 2024)
Millets have been a staple in human diets for millennia, particularly in Africa and Asia. The most commonly cultivated millets globally, with a significant presence in India, include pearl millet, finger millet, foxtail millet, Indian barnyard millet, kodo millet, little millet, and proso millet. In Ayurveda, millets are classified under Dhanya Varga and are known by different names such as Trina Dhanya, Kudhanya, and Kshudra Dhanya in various Samhitas. Additionally, indigenous communities have traditionally used millets for medicinal purposes and to combat hunger. Millets are a hardy crop, thriving in poor soil conditions with minimal rainfall. The small "grain" is free from gluten and filled with essential vitamins and minerals. Millet grain is extremely nourishing, containing high-quality protein, abundant minerals, dietary fiber, phytochemicals, and vitamins. When comparing the nutritional content of millets to that of rice and wheat, it is evident that foxtail millet, proso millet, and pearl millet have higher protein content than wheat. Millets have emerged as a potential solution to address the present challenges in agriculture, food security, and public health. This is primarily due to the decline in the production of primary staple crops caused by shifting agro-climatic conditions. However, millets have demonstrated remarkable adaptability and possess a highly nutritious composition, making them a promising alternative.